Applying The Six Sigma Methodology To Enhance Accounting Information Quality And Boost Tax Revenue- An Applied Study - Sami Lateef Jihadi; Nuha Aadi Abd Ali; Ali Mamood Amed (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of the research was to boost tax revenues and enhance the accuracy of accounting information by implementing the SIX SIGMA technique. In order to gather primary data from the study sample, which consisted of (148) personnel in the quality and internal audit departments or the representatives of them in the Iraqi General Tax Authority, a questionnaire with (148) items was created. The study came to several conclusions, chief among them being that Six Sigma standards—which include senior leadership commitment and support, feedback and measurement, continuous improvement, processes and systems, and human resources—have a major influence on enhancing the degree of accounting information quality and collecting tax revenue (internal audit activities management, risk management evaluation, planning and carrying out the audit procedure, and sharing the findings) at a significant level (0.05). The report advised focusing on the Six Sigma idea and showcasing its potential for reducing mistakes, enhancing the caliber of accounting data, and boosting tax revenues.